Nilai filosofis dalam Chanoyu - Kastuti, Teti Indriati (Japanese Research on Linguistics, Literature, and Culture, 2018)
This research is entitled Philosophical Value in Chanoyu. There are three problems formulated in this research, as follows; 1) Is there any philosophical value in Chanoyu? 2) How is philosophical value in seven rules of Sen no Rikyu (shichisoku), 3) How is philosophical value in four basic spiritual principles of Sen no Rikyu?. This research aims 1) to find out the illustration of philosophical value in Chanoyu, 2)to find out the illustration of philosophical value in seven rules of Sen no Rikyu, 3) to find out the illustration of philosophical value infour basic spiritual principles of Sen no Rikyu (shiki). This research employs descriptive method by developing data and real fact and literature method by using data from the available literature. The research results conclude that there are philosophical values in Chanoyu, philosophical value in seven rules of Sen no Rikyu and four basic spiritual principles of Sen no Rikyu are the basis of the highest idealism in the practice of Chanoyu.Â Keyword: chanoyu, philosophical value, shichisoku, shiki